2017
DOI: 10.1146/annurev-micro-090816-093813
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Trajectories to Antibiotic Resistance

Abstract: The ability to predict the evolutionary trajectories of antibiotic resistance would be of great value in tailoring dosing regimens of antibiotics so as to maximize the duration of their usefulness. Useful prediction of resistance evolution requires information about (a) the mutation supply rate, (b) the level of resistance conferred by the resistance mechanism, (c) the fitness of the antibiotic-resistant mutant bacteria as a function of drug concentration, and (d) the strength of selective pressures. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
179
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(186 citation statements)
references
References 123 publications
(128 reference statements)
5
179
0
2
Order By: Relevance
“…The prospect of using reproducible evolutionary trajectories to resistance as a tool to control the emergence and persistence of AMR is a growing area of research [2,3]. One of the prerequisites for translation of these ideas to the clinic in the form of prescription policy advice is robust and reproducible data which can convince clinicians and policy makers that what is seen in the laboratory is likely to occur in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prospect of using reproducible evolutionary trajectories to resistance as a tool to control the emergence and persistence of AMR is a growing area of research [2,3]. One of the prerequisites for translation of these ideas to the clinic in the form of prescription policy advice is robust and reproducible data which can convince clinicians and policy makers that what is seen in the laboratory is likely to occur in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, and in direct response to the global rise in antimicrobial resistant (AMR) pathogenic bacteria, there has been an increased interest in how resistance develops and becomes fixed within a bacterial population. This ranges from the effect of antimicrobials entering the environment following use in humans and animals [1] to understanding the evolution of antimicrobial resistance and the selective pressure from antimicrobials [2,3], with a view to developing new strategies to prevent development of AMR in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria can become resistant in two main ways: the first is that they undergo a genetic mutation that changes an antimicrobial target in some way (Hughes and Andersson 2017) and the second is that they acquire resistance genes from another bacterium or the environment. While the first of these are chance events, the sheer number of bacteria means that such mutations probably occur quite frequently.…”
Section: Resistancementioning
confidence: 99%
“…It has been proposed that this is due to compensatory mutations (Maisnier-Patin and Andersson 2004). Compensatory mutations relieve the cost of resistance through partial restoration of the impacted phenotype (Reynolds 2000; Szamecz et al 2014; Hughes and Andersson 2017) and have been consistently found in laboratory experiments (Schrag et al 1997; Reynolds 2000; Maisnier-Patin and Andersson 2004). But, compensatory mutations are often absent from clinical strains of antibiotic resistant bacteria (Andersson and Levin 1999; MacLean and Vogwill 2015), suggesting that something more is at play.…”
Section: Introductionmentioning
confidence: 96%